2017
DOI: 10.1038/s41598-017-09651-x
|View full text |Cite
|
Sign up to set email alerts
|

An automated compound screening for anti-aging effects on the function of C. elegans sensory neurons

Abstract: Discovery of molecular targets or compounds that alter neuronal function can lead to therapeutic advances that ameliorate age-related neurodegenerative pathologies. Currently, there is a lack of in vivo screening technologies for the discovery of compounds that affect the age-dependent neuronal physiology. Here, we present a high-throughput, microfluidic-based assay for automated manipulation and on-chip monitoring and analysis of stimulus-evoked calcium responses of intact C. elegans at various life stages. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…While several opensource autosamplers and Fraction Collectors have been developed for applications such as spectroscopy and gas chromatography, [49][50][51] the field of microfluidics has relatively few examples of autosampler and Fraction Collector usage, with the majority of these examples employing commercial solutions. [52][53][54][55][56][57] More recent work has demonstrated a fully automated, low-cost open-source autosampler for microfluidics that is compatible with gravity-and vacuum-driven flow. 58 The ability to sample with positive, pressure-driven flow builds on the advances of this platform.…”
Section: Discussionmentioning
confidence: 99%
“…While several opensource autosamplers and Fraction Collectors have been developed for applications such as spectroscopy and gas chromatography, [49][50][51] the field of microfluidics has relatively few examples of autosampler and Fraction Collector usage, with the majority of these examples employing commercial solutions. [52][53][54][55][56][57] More recent work has demonstrated a fully automated, low-cost open-source autosampler for microfluidics that is compatible with gravity-and vacuum-driven flow. 58 The ability to sample with positive, pressure-driven flow builds on the advances of this platform.…”
Section: Discussionmentioning
confidence: 99%
“…While several open-source autosamplers and fraction collectors have been developed for applications such as spectroscopy and gas chromatography, [43][44][45] the field of microfluidics has relatively few examples of autosampler and fraction collector usage, with the majority of these examples employing commercial solutions. [46][47][48][49][50] More recent work has demonstrated a fully automated, low-cost open-source autosampler that uses gravity-driven flow to feed microfluidic devices, 51 as well as a gasketed dual-lumen injector for pressure-driven microfluidic sampling that was similar to our solution but with a manual XY-stage. 33,[52][53][54][55][56] The micrIO platform merges these two advances into an open-source platform for fully automated, pressure-driven multiwell plate sampling while additionally providing fraction collection capabilities and Python software to coordinate with other devices commonly used in microfluidics.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have demonstrated that PTZ responsiveness is unaffected by DMSO concentrations up to 1%, thereby facilitating screening of DMSO-solubilised compound libraries. Additional streamlining of the screening process could potentially be achieved using robotic systems for automated culturing and handling of nematodes, which are also adaptable for micro-titre plate configurations ( Bazopoulou et al, 2017 ; Boyd et al, 2010 ; Xian et al, 2013 ). Although we have demonstrated that precise age synchronization is not essential for our platform, since 1- to 3-day-old adult worms respond similarly to PTZ, current technologies enabling the sorting of C. elegans by age and/or size could potentially be used to further enhance the assay by facilitating automated selection of young adult nematodes ( Boyd et al, 2010 ; Pulak, 2006 ; Rezai et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%